HISTORY OF TOURISM (Uzbek Scholar Journal, 2022)
Tourism, the act and process of spending time away from home in pursuit of recreation, relaxation, and pleasure, while making use of the commercial provision of services. As such, tourism is a product of modern social arrangements, beginning in western Europe in the 17th century, although it has antecedents in Classical antiquity.